ANALISIS PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN MARKOWITZ DAN SINGLE INDEX MODEL PADA SAHAM JAKARTA ISLAMIC INDEX - Irsyaad Rachmatullah (2021)
This research is a quantitative descriptive study which aims to determine the optimal portfolio composition of stocks that are consistently listed on the Jakarta Islamic Index (JII) from the 2018 - November 2020 period. By using the Markowitz analysis method and the Single Index Model, and then looking at the portfolio performance of both methods. The results of this study are: (1) in the Markowitz method, 2 stocks that form the optimal portfolio are obtained, namely: ANTM (51%), and BRPT (49%). With a level of expected return portfolio of 0,0083 or 0,83%, and a portfolio risk level of 0,0659 or 6,59%. (2) in the Single Index Model method, 4 stocks that form the optimal portfolio are obtained, namely: BRPT (35,75%), ANTM (35,27%), INCO (25,07%), and WIKA (3,9%). With a level of expected return portfolio of 0,0075 or 0,75%, and a portfolio risk level of 0,0110 or 1,10%. (3) performance Markowitz portfolio has a value sharpe index of 0,1116, treynor index of 0,0066, and jensen index of 0,0052. (4) the performance of Single Index Model portfolio has a value sharpe index of 0,5919, treynor index of 0,0042, and jensen index of 0,0035.